Plin‐amiR, a pre‐microRNA‐based technology for controlling herbivorous insect pests. Issue 9 (10th March 2020) - Bally, Julia; Fishilevich, Elane; Doran, Rachel L.; Lee, Karen; de Campos, Samanta Bolzan; German, Marcelo A.; Narva, Kenneth E.; Waterhouse, Peter M.
Summary: The cotton bollworm, Helicoverpa armigera, is a major insect pest for a wide range of agricultural crops. It causes significant yield loss through feeding damage and by increasing the crop's vulnerability to bacterial and fungal infections. Although expression of Bacillus thuringiensis (Bt) toxins in transgenic crops has been very successful in protecting against insect pests, including H. armigera, field‐evolved resistance has occurred in multiple species. To manage resistant populations, new protection strategies must be continuously developed. Trans‐kingdom RNA interference (TK‐RNAi) is a promising method for controlling herbivorous pests. TK‐RNAi is based on delivering dsRNA or hairpin RNA containing essential insect gene sequences to the feeding insect. The ingested molecules are processed by the insect's RNAi machinery and guide it to silence the target genes. Recently, TK‐RNAi delivery has been enhanced by expressing the ds‐ or hpRNAs in the chloroplast. This compartmentalizes the duplexed RNA away from the plant's RNAi machinery, ensuring that it is delivered in an unprocessed form to the insect. Here, we report another alternative approach for delivering precursor anti‐insect RNA in plants. Insect pre‐microRNA (pre‐miR) transcripts were modified to contain artificial microRNAs (amiRs), targeting insect genes, and expressed in transgenic Nicotiana benthamiana plants. These modified pre‐miRs remained largely unprocessed in the plants, and H. armigera feeding on leaves from these plants had increased mortality, developmental abnormalities and delayed growth rates. This shows that plant‐expressed insect pre‐amiRs (plin‐amiRs) are a new strategy of protecting plants against herbivorous insects.